Clinical features, treatments and outcomes of influenza A (H1N1) 2009 among the hospitalized patients in the clinic for infectious diseases in Novi Sad - Čanak Grozdana; Kovačević Nadica; Vukadinov Jovan; Turkulov Vesna; Sević Siniša; Doder Radoslava; Somborac Stevan; Potkonjak Aleksandar (Vojnosanitetski Pregled)
Background/Aim. Most infections caused by influenza A (H1N1) 2009 virus are presented by mild respiratory symptoms. However, some patients required admission to the intensive care unit (ICU). In this article we aimed to describe the clinical and laboratory characteristics of the patients with influenza A (H1N1) 2009, antiviral therapy use, the disease outcome and risk factors associated with the severe disease. Methods. The patients with the signs and symptoms of novel influenza A (H1N1) 2009, admitted to the Clinic for Infectious Disease in Novi Sad, were evaluated. The study included 293 patients hospitalized between October 2009 and February 2010. Basic demographic data, underlying medical conditions, clinical signs and symptoms, duration of the disease before the admission, laboratory tests, radiographic findings, treatment, and the final outcome (survived, died) were all noted. Factors associated with severe disease requiring ICU admission were determined by comparing the ICU cases with control groups of the patients admitted to the hospital but not to ICU. Results. The average age of the patients was 32.72 years. A total of 114 (38.9%) of the patients had an underlying medical condition. Asthma and chronic obstructive pulmonary disease were present in 44 (15.01%) of the patients, chronic cardiovascular diseases in 28 (9.56%), diabetes mellitus in 16 (5.46%), malignity in 15 (4.44%) of the patients and 11 (3.75%) of the patients were pregnant. Fever was registered in 282 (96.24%), myalgias in 119 (40.61%), headache in 48 (16.38%), cough in 240 (81.91%), sore throat in 25 (8.53%), runny nose and sneezing in 17 (5.8%) and dyspnea in 110 (37.54%) of the patients. A total of 192 (65.53%) had radiological findings that were consistent with pneumonia. A total of 154 (56.61%) of the patients received antiviral therapy within 48 h. A total of 280 (96.24%) patients were discharged and 13 (4.44%) were transferred to ICU. Fatal outcome was noticed in 2/13 (15.3%) ICU treated patients and 11/13 (84.7%) patients survived. The median time from the onset of illness to the initiation of antiviral treatment was 7.1 days for the patients admitted to ICU and 3.2 days for non-ICU patients (p < 0.05). Low blood oxygen saturation (SaO2 ≤ 92%) was more common in ICU admitted patients, 10/13 (76,92%), compared to 28/280 (10%) non-ICU admitted ones (p < 0.01). Serum C-reactive protein (CRP) levels > 200 mg/L were noticed in 9/13 (69.23%) patients admitted to ICU and 85/280 (30.35%) patients who were not (p < 0.05). Conclusion. Most novel influenza A (H1N1) 2009 infections presented mild respiratory disease. Prompt antiviral therapy in patients with A (H1N1) virus infection seem to be the best approach to avoid serious form of the disease. Special attention should be payed to patients having low level of peripheral oxygen saturation and raised CRP serum level.